Prophetic Values in the Principal's Leadership Style at SDN 1 Ranomeeto, Konawe Selatan - Badarwan Badarwan; Supriadin Supriadin (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This article aims to analyze the prophetic values in the leadership of the principal at SDN 1 Ranomeeto, which include: 1) deliberation as a way of making decisions; 2) be open; 3) teacher capacity building; 4) create a conducive working climate; 5) understand the condition of the teacher; 6) increase teacher participation; 7) provide coaching and counseling. This research is a qualitative research using a narrative approach. Data collection techniques were carried out by interview, observation and documentation. Data analysis through the process of reduction, presentation of data and drawing conclusions as well as checking the validity of the data technique through triangulation of techniques, sources and time. The results showed that: 1) Various problems and school agendas were resolved through deliberation forums; 2) the principal's open attitude was shown by accepting input, suggestions and criticism, especially from teachers; 3) teacher capacity building is a priority in school programs; 4) the work climate is created by building a family atmosphere, 5) the shortcomings and strengths of teachers are known through the supervision process, 6) various school activities always involve teachers; 7) coaching and counseling is carried out in enforcing school discipline, increasing teacher competence and performance. The implication of this study, the author suggests the need for further research related to prophetic education for school residents.Keywords: Prophetic Values, Educational Leadership